Authentication System for Medical Images Using Hilbert Numbering - Syifak Izhar, Hisham; Jasni, Mohamad Zain; Nurul Wahidah, Arshad; Siau-Chuin, Liew; Nasrul Hadi, Johari; Gran, Badshah (2014)
Medical image is seen as one of crucial data that demand for authentication method as it is highly confidential and used in insurance claim, evidence of jurisdiction and personal identification. Nowadays, Hospital Information System (HIS) is used widely at hospitals and clinical departments and it handles thousands of crucial electronic data in medical. We have introduced a fragile watermarking method using spiral manner numbering which showed a good numbering system and excellent embedding, but due to the technique, it only embedded in square shape. We enhanced the scheme to the Hilbert numbering scheme, which is more compatible with medical image modalities, which is not only specific to square shape of image but applicable to all kinds of image.